"COMMUNICATIVE DIFFICULTIES OF RUSSIAN AND ARMENIAN ADOLESCENTS: A SOCIOCULTURAL ASPECT" - Avanesyan, H. M.; Asriyan, E. V.; Samokhvalova, A. G. (Modern Psychology, 2019)
The article presents the results of a cross-cultural study of the communication difficulties of adolescents from Armenia and Russia. The general age-related communication difficulties characteristic of the adolescent stage of ontogenesis were revealed; as well as the sociocultural, differences of the communicative difficulties of Russian and Armenian adolescents. In experiment they were participated 280 adults, two groups aged 14-15 and 16-17 years. The test results were processed according to the statistical formula of the Mann–Whitney U test. Being focused on the context of the situations of communication, respondents described the difficulties encountered in the process of communication with adults and peers.
Keywords: adolescent, communication, communication difficulties, socio-cultural environment, cross-cultural differences